2006
DOI: 10.1007/s11255-005-4971-x
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise shock wave lithotripsy: Results of initial study for the treatment of urinary stones in childhood

Abstract: Stepwise shock wave lithotripsy was an effective procedure for the treatment of urinary calculi in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Extracorporeal shock wave lithotripsy has been demonstrated to be effective and safe for the treatment of pediatric urolithiasis [27,28]. This treatment modality neither causes renal scars nor affects renal function and linear growth [29].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave lithotripsy has been demonstrated to be effective and safe for the treatment of pediatric urolithiasis [27,28]. This treatment modality neither causes renal scars nor affects renal function and linear growth [29].…”
Section: Discussionmentioning
confidence: 99%
“…4 To our knowledge, our randomized trial is the first to examine the impact of step-wise increase of output voltage during SWL on outcome in humans. We studied whether a stepwise increase in output energy during SWL yielded a better success rate than constant output of energy during SWL without increased morbidity.…”
Section: Demirci Et Al 1408mentioning
confidence: 99%
“…3 Step-wise SWL was effective in the management of urinary calculi in 31 children without increased morbidity and with acceptable success rates. 4 In our clinical study, we aimed to compare the results of conventional and step-wise SWL procedures in the management of urinary calculi. stones were detected by plain radiography of the kidneys, ureters and bladder, urinary system ultrasonography, and intravenous urography.…”
Section: Introduction S Ince the Clinical Introduction Of Extracorporealmentioning
confidence: 99%
“…Demirci et al [7,8] have reported similar results in clinical studies. They suggested that increasing the intensity of shockwaves could compensate for the screening effect, a phenomenon whereby shockwaves are scattered and attenuated by fragmented stone powders accumulating around residual large pieces.…”
Section: Introductionmentioning
confidence: 54%